Association of influenza vaccine and risk of recurrence in patients undergoing curative surgery for colorectal cancer. (2nd November 2021) - Gögenur, Mikail; Fransgård, Tina; Krause, Tyra Grove; Thygesen, Lau Caspar; Gögenur, Ismail
Abstract: Background: There is increasing evidence that the inactivated influenza vaccine contains immunostimulatory properties that favor cytotoxicity and benefit survival in large population-based studies. This study aimed to determine whether an influenza vaccine was associated with risk of recurrence, overall mortality, and disease-free survival in patients undergoing curative surgery for colorectal cancer. Material and methods: We performed a register-based study based in Denmark in the period 2009–2015. The primary outcome was a risk of recurrence, while the secondary outcomes were overall mortality and disease-free survival. Results: A total of 9869 patients were included, with 5146 patients receiving an influenza vaccine between one year before and six months after surgery. In a multivariate Cox regression model, there was no association with risk of recurrence (HR 0.94, 95% CI 0.85–1.05), overall mortality (HR 0.95, 95% CI 0.87–1.03), and disease-free survival (HR 1.01, 95% CI 0.94–1.09). In patients receiving the vaccine between six and twelve months before surgery, we found an association to decreased risk of recurrence (HR 0.78, 95% CI 0.67–0.91) but no association with overall mortality (HR 1.04, 95% CI 0.93–1.17) or disease-free survival (HR 0.97, 95% CI 0.88–1.07). Subgroup analysis of patients revealed contradictory results. Conclusion: We believe that this study's findings support the need for further clinical studies to investigate the causal effects of the influenza vaccine on oncological outcomes.